THE WESTERN PANSKY TUNDRA LAYERED INTRUSION, KOLA PENINSULA: DIFFERENTIATION MECHANISM AND SOLIDIFICATION SEQUENCE - Latypov R.M.; Mitrofanov F.P.; Skiba V.I.; Alapieti T.T. (My University, 2001)
Hypotheses of the genesis of the Western Pansky Tundra layered intrusion differ in the interpretation of some key problems in the petrology of the pluton. These include: (1) whether the pluton is an individual geologic body or a part of the larger Pansky and Fedorovo-Pansky massifs; (2) whether it is a mono- or polyphase pluton, (3) what is the crystallization trend of the parental melt; (4) which processes were responsible for the development of the two critical zones of the intrusion, the Lower and the Upper Layered Unit (LLU and ULU, respectively); and (5) whether the magnetite gabbro is a foreign or syngenetic rock. Based on the analysis of preexisting data, a model was proposed for the evolution of the Western Pansky Tundra intrusion as an individual pluton. The massif is proved to consist of two intrusive phases, the first of which comprises the lower, gabbronorite portion of the massif, from its bottom to the Upper Layered Unit, and the other extends from the Upper Layered Unit to the overlying gabbronorite. The parental melt of the first intrusive phase corresponded to unsaturated tholeiite (an(L) = 65%, f(L) = 23%). The crystallization of this phase proceeded from bottom to top and, later, when the chamber was divided into a series of smaller reservoirs (subchambers), from their walls to centers. The genesis of the Lower Layered Unit is related to a temporary opening of the chamber and its replenishment with batches of melt whose composition was close to that of the parental magma. The differentiation trend of the parental melt of the first intrusive phase was characterized by the following crystallization succession of minerals: Pl + Opn (norite) --> Pl + Opx + Cpx (gabbronorite) --> Pl + Cpx + Opx + Pig (gabbronorite with inverted pigeonite) --> Pl + Opx + Opx + Pig + Mgt (magnetite gabbro with inverted pigeonite). The second intrusive phase was produced by a later voluminous melt portion, whose composition was less evolved than that of phase I (an(L) - 75%, f(L) = 19%). The crystallization of the original melt of phase II started with the cotectic assemblage Pl + Opx + Cpx (gabbronorite). Later, brief disturbances of the differentiation trend occurred at the level of olivine-bearing beds within the Upper Layered Unit because of the injection of melt batches of olivine tholeiite composition. The crystallization succession in these beds was generally as follows: Pl (+/- Ol) (olivine leucogabbro) --> Pl + Ol (troctolite) --> Pl + Ol + Opx(olivine norite) --> Pl + Opx (norite) --> Pl + Opx + CPx (gabbronorite).